PERLINDUNGAN HUKUM INVESTOR ASET KRIPTO DI INDONESIA TERHADAP PRAKTIK MANIPULASI PASAR - Maulana Iskhaq Wicaksono; Dita Perwitasari (Universitas Labuhanbatu, 2026)
The transfer of cryptocurrency supervision from Bappebti to the Financial Services Authority (OJK) through Law No. 4 of 2023 (P2SK Law) is expected to bring investor protection standards in line with other financial sectors. However, this transition leaves a legal loophole in its implementing regulation, POJK No. 27 of 2024, which does not explicitly prohibit market manipulation practices. This study aims to analyse these legal gaps and formulate ideal protections. Using a normative juridical method that combines three approaches, namely legislation, comparison, and conceptual approaches, this study compares current crypto regulations with the Capital Market Law. The results show that POJK No. 27/2024 only focuses on institutional and operational aspects, without providing specific prohibitions on manipulative schemes such as pump and dump or wash trading. Therefore, this study recommends four steps for legal reconstruction: adopting prohibitive norms from the Capital Market Law, adapting market surveillance technology, implementing deterrent sanctions, and establishing a whistleblowing system mechanism, in order to ensure legal certainty for investors in Indonesia.Keywords: Cryptocurrency; Market Manipulation; Investor Protection; Legal Certainty